1981
DOI: 10.1002/dev.420140305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reciprocal cross‐fostering on aggression of female mice toward lactating strangers

Abstract: Reciprocal cross-fostering of mice was carried out between an inbred strain (C57 BL/6) in which the female showed a particular form of aggression toward lactating female intruders, and a strain (C3H/He) which proved to lack totally this type of attack. In adulthood, cross-fostered females of the 2 strains and their controls were submitted to a series of aggression tests. They encountered in the test situation either a strange lactating female of their own strain of the foster strain. No differences in aggressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…juvenile play and social approach, are in accord with several previous studies that found no effect of cross‐fostering on other categories of social behaviors. It was reported that inter‐strain cross‐fostered B6 and C3H females exhibited maternal aggression akin to their biological mothers, suggesting that maternal defensive response towards a stranger is largely shaped by genetic factors (Haug and Pallaud, 1981). Similarly, it has been shown that female rhesus macaques exhibited affiliative and aggressive behaviors that are more similar to their biological mothers than to foster mothers (Maestripieri, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…juvenile play and social approach, are in accord with several previous studies that found no effect of cross‐fostering on other categories of social behaviors. It was reported that inter‐strain cross‐fostered B6 and C3H females exhibited maternal aggression akin to their biological mothers, suggesting that maternal defensive response towards a stranger is largely shaped by genetic factors (Haug and Pallaud, 1981). Similarly, it has been shown that female rhesus macaques exhibited affiliative and aggressive behaviors that are more similar to their biological mothers than to foster mothers (Maestripieri, 2003).…”
Section: Discussionmentioning
confidence: 99%